Study and exploration of the pharmacokinetics of traditional Tibetan medicine Ruyi Zhenbao tablets after single and long-term administration - Hou, Hongping; Chen, Tengfei; Xu, Ziying; Yu, Zihui; Wang, Caixia; Liu, Rongxia; Peng, Bo; Yang, Wei; Li, Feng; Che, Xiangyi; Li, Bing; Wang, Yu; et al. (Frontiers in Pharmacology, 2022)
Tibetan medicine is one of the oldest traditional medicine systems in the world. Taking the Ruyi Zhenbao tablet (RYZB) as an example, which is a widely used classic oral Tibetan medicine, this article discusses the pharmacokinetics of single administration and long-term treatment, analyzed its metabolic properties and tissue distribution in vivo. After single administration, blood samples were collected before administration and different time points after administration in different groups of rats. In the study of long-term treatment effects, blood samples were collected from the animals in each group on days 1, 15, 30, and on day 15 after withdrawal. The results showed that after a single administration, the dose change had no significant effect on the T1/2 and Tmax of agarotetrol, isoliquiritigenin, and piperine (p > 0.05). There was a certain correlation between the increase in AUC0-t and the Cmax of agarotetrol, isoliquiritigenin, piperine, and the increase in dosage; dose range of 0.225–0.900 g/kg. There were no significant differences in Cmax and AUC0-t of ferulic acid at different doses (p > 0.05). Meanwhile, there was no significant sex-based difference in the pharmacokinetic parameters of these four components in rats. After long-term administration, the distribution agarotetrol in various tissues of rats was kidney > liver > heart > brain; The tissue distribution in low- and medium-dose groups of isoliquiritigenin was liver > kidney > heart > brain, and in the high-dose group kidney > liver > heart > brain. The tissue distribution of piperine in each dose group was liver > kidney > heart > brain, and that of ferulic acid in each dose group was kidney > liver > heart > brain. Through the establishment of the previously developed methodology, the pharmacokinetic properties of RYZB were analyzed after single administration and long-term administration. Our findings confirmed this approach for the exploration and establishment of a pharmacokinetic evaluation of Tibetan medicine, to support its guiding role in clinical application, but also to accelerate research into Tibetan medicine theory and medicine and to provide a solid foundation for the translation of Tibetan medicine throughout the world.